Trajectory Planning for a Dual-Arm Planar Free-Floating Manipulator using RRTControl - Serrantola, Wenderson Gustavo; Grassi, Valdir (2019 19th International Conference on Advanced Robotics (ICAR), 2019)
Due to the increasingly important role of space manipulators in orbital operations and the difficulties encountered in trajectory planning as a consequence of the dynamic coupling between the robot arm and the robot base, this paper proposes to use the RRTControl algorithm, an adaptation of the RRT algorithm used when the system is subject to differential constraints, for trajectory planning of a Dual-Arm Planar Free-Floating Manipulator (FFSM) in joint space with static obstacle avoidance. The FFSM was modeled using the Dynamically Equivalent Manipulator approach, and The Open Motion Planning Library (OMPL) was used as the basis for system implementation. The results of simulations demonstrate that the RRTControl algorithm was able to solve the problem of trajectory planning for the FFSM with and without an obstacle.